Factors influencing franchisees' business performance : a study on the Nigerian franchise system - Adams Adeiza (2017)
This study explores factors that influence franchisees' business performance in Nigeria. Using a model of factors influencing franchise system performance as a conceptual framework, an extensive review and synthesis of literature was done. The literature synthesis led to the development of four (4) research issues and a preliminary theoretical framework for the research. The issues and the framework were subjected to empirical exploration using data collected through in-depth interviews. The research was conducted in two stages: preliminary stage and main stage. A total of thirty-two (32) purposively selected franchisees participated in the study; six (6) in the preliminary stage and twenty-six 26) in the main stage. Data were managed and analysed using NVivo version 11. Through the analysis, a total of twenty-one (21) factors were confirmed as having influence on franchisees business performance in Nigeria. Fourteen (14) of these factors are as identified in the preliminary theoretical framework while seven (7) were newly found in the study. Based on the findings of this study, eight (8) key conclusions were drawn. It was concluded that four (4) major issues and a total of twenty-one 21) factors have influence on franchisees business performance in Nigeria. Among these factors are four (4) business format factors, six (6) contract factors, six (6) relationship quality factors and five (5) franchisees attitude and skill factors. Being the first comprehensive attempt to study the practice of franchising in Nigeria, this study makes contributions to franchising literature in three important ways, namely; it reaffirms current understanding, identifies new insights and enhances contextual knowledge of the business model. Finally, the study highlights four (4) major managerial implications and offers recommendations that could address these implications.